Impact of the COVID pandemic on the modern economy - Korus, Е. С. (ТДАТУ, 2020)
The pandemic led to the closure of enterprises in countries with a high percentage of cases, to a sharp increase in demand for everyday products, to speculation in the market for certain goods: antiviral drugs, sanitary masks, disinfectants. Also, there is a significant increase in demand for food delivery services due to the reluctance of many citizens to leave their homes.
Keywords: COVID- 19 pandemic; coronacrisis; delivery services